The Editorial Note - Andindilile, Michael (University of Dar es Salaam Library Journal, 2024)
On behalf of the editorial committee and the editorial board, I have the privilege to present to you our current issues of December 2024. The diversity of the articles in our current issues reflects different LIS dimensions.